Autosomal dominant retinitis pigmentosa locus on chromosome 19q in a Japanese family. Issue 11 (November 1995) - Xu, S; Nakazawa, M; Tamai, M; Gal, A
Abstract : A large four generation Japanese family was studied, in which autosomal dominant retinitis pigmentosa (ADRP) of very variable expression was segregating. Positive lod scores with maxima between 1.557-5.118 at theta = 0.00, strongly suggestive of linkage, were obtained for KLK, D19S180, D19S418, and D19S254 on chromosome 19q. Recently, an ADRP locus has been mapped to the same region in a British family, in which, again, several members subjectively had no clinical evidence of the disease although they had both an affected parent and an affected child.